Intensive induction chemotherapy followed by myeloablative chemotherapy with autologous hematopoietic progenitor cell rescue for young children newly‐diagnosed with central nervous system atypical teratoid/rhabdoid tumors: The head start III experience. Issue 1 (11th August 2013) - Zaky, Wafik; Dhall, Girish; Ji, Lingyun; Haley, Kelley; Allen, Jeffrey; Atlas, Mark; Bertolone, Salvatore; Cornelius, Albert; Gardner, Sharon; Patel, Ramesh; Pradhan, Kamnesh; Shen, Violet; et al.
Abstract Background Atypical teratoid/rhabdoid tumor (AT/RT) of the central nervous system (CNS) is a rare embryonal neoplasm of early childhood with dismal outcome and no current uniformly accepted treatment. Given its highly aggressive nature and predilection for dissemination at diagnosis, intensive multimodal therapy is required. Materials and Methods Nineteen children with newly diagnosed CNS AT/RT were treated on the head start (HS) III protocol. Treatment consisted of surgical resection, 5 cycles of induction chemotherapy, followed by consolidation with myeloablative chemotherapy and autologous hematopoietic progenitor cell rescue (AuHCR). Irradiation was given following recovery from consolidation based on patient age, disease extent at diagnosis, and treatment response to induction. Results Nineteen children (median age of 14 months) were treated on HS III between 2003 and 2009. Only four finished induction and three proceeded to consolidation. There are presently four survivors at 40, 42, 46, and 79 months from study enrollment. Eleven patients experienced tumor progression at a median time to progression of 4.1 months of whom 10 died with a median time from progression to death of 2.6 months. Five toxic deaths occurred, three of them while on the study. The 3‐year event‐free survival (EFS) and overall survival (OS) for the whole group was 21 ± 9% and 26 ± 10%, respectively. Five patients received irradiation at progression with only one long‐term survivor. Conclusion A minority of children with CNS AT/RT treated on HS III may be long‐term survivors without irradiation. More effective therapies are desperately needed. Pediatr Blood Cancer 2014;61:95–101. © 2013 Wiley Periodicals, Inc.